Imaging system for tongue diagnosis - Kum, Kenneth Jia Ming. (2013)
Tongue color diagnosis is a common method used by physicians who practice Traditional Chinese Medicine (TCM). It is used to diagnose a patients well being and health by analyzing the color of different regions of the tongue as in TCM it is believed that the conditions of specific parts of the body can be reflected by the different regions of the tongue. This study makes use of both digital software and hardware design to provide an effective method of capturing a color accurate image of the patient’s tongue. The objective of this iteration of the project is to identify the relationship between the LAB colour space values obtained from digital imaging software processing actual sample data collected at a TCM clinic and the common colours TCM physicians encounter in their diagnosis of patients. From the data and results obtained, 7 distinct colour groups were abled to be identified and they each grouped in different configurations within the colour space, giving them different “shapes”. From this data, the outer limits of the different colour groups were identified and thus providing a clear view of the regions of LAB values that are associated to each individual colour group. This information obtained will be a starting point for further improve upon the diagnosis software and will provide a colour model for TCM physicians to accurately determine a tongue’s colour based on actual scientific data rather than on personal judgment.